2019
DOI: 10.1158/1078-0432.ccr-18-1382
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Dye-Labeled Anti-Prostate Stem Cell Antigen Minibody Enables Real-Time Fluorescence Imaging and Targeted Surgery in Translational Mouse Models

Abstract: Purpose: The inability to intraoperatively distinguish the primary tumor, as well as lymphatic spread, increases the probability of positive surgical margins, tumor recurrence, and surgical toxicity. The goal of this study was to develop a tumor-specific optical probe for real-time fluorescence-guided surgery. Experimental design: A humanized antibody fragment against PSCA (A11 minibody, A11 Mb) was conjugated with a near-infrared fluorophore, IRDye800CW. The integrity and binding of the probe to PSCA were c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 41 publications
(45 reference statements)
0
20
2
Order By: Relevance
“…To this end, a free cysteine residue is incorporated in the targeting moiety's structure at the location of predilection, such as the C- or N-terminus of protein scaffolds, peptides and small antibody fragments (Sun et al, 2005; Massa et al, 2014). Antibodies and larger fragments such as minibodies and diabodies can furthermore be partially reduced, freeing the sulfhydryl residues of more exposed disulfide bridges for conjugation (Olafsen et al, 2004; Sonn et al, 2016; Tsai et al, 2018; Zettlitz et al, 2018; Zhang et al, 2018). Many other site-specific methods have gained popularity over the last years, such as the azide-alkyne cycloaddition-click chemistry (Li et al, 2014), enzymatic modification of peptide tags (e.g., transglutaminase-, sortase-, or intein-mediated conjugation) (Massa et al, 2016a), incorporation of unnatural amino acids for biorthogonal conjugation or the use of linking peptides such as the SPY/SPYcatcher method (Massa et al, 2016b; Alam et al, 2018).…”
Section: Molecular-targeted Fluorescent Tracersmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, a free cysteine residue is incorporated in the targeting moiety's structure at the location of predilection, such as the C- or N-terminus of protein scaffolds, peptides and small antibody fragments (Sun et al, 2005; Massa et al, 2014). Antibodies and larger fragments such as minibodies and diabodies can furthermore be partially reduced, freeing the sulfhydryl residues of more exposed disulfide bridges for conjugation (Olafsen et al, 2004; Sonn et al, 2016; Tsai et al, 2018; Zettlitz et al, 2018; Zhang et al, 2018). Many other site-specific methods have gained popularity over the last years, such as the azide-alkyne cycloaddition-click chemistry (Li et al, 2014), enzymatic modification of peptide tags (e.g., transglutaminase-, sortase-, or intein-mediated conjugation) (Massa et al, 2016a), incorporation of unnatural amino acids for biorthogonal conjugation or the use of linking peptides such as the SPY/SPYcatcher method (Massa et al, 2016b; Alam et al, 2018).…”
Section: Molecular-targeted Fluorescent Tracersmentioning
confidence: 99%
“…A recent study demonstrated the use of an anti-(human) PSCA minibody, called A11, conjugated with IRDye800CW in different mouse models. Subcutaneous, orthotopic and intramuscular implanted tumors and tumor positive lymph nodes could be clearly visualized, even in knock-in models expressing the human homolog of PSCA (Zhang et al, 2018). Furthermore, fluorescence-guided resection of intramuscular tumors, revealed superior overall survival compared to conventional white light surgery (Zhang et al, 2018).…”
Section: Molecular-targeted Fluorescent Tracersmentioning
confidence: 99%
“…Unlike mAbs, antibody fragments with short half-life and strong permeability are more suitable for tumour imaging [45,46]. Antibody fragment-based tumour imaging is widely used for (1) non-invasive detection of tumours; (2) real-time guidance of surgery; (3) monitoring of tumourigenic receptor expression status, tumour development status, and tumour treatment prognosis [47,48]. At present, imaging diagnosis based on antibody fragments is rapidly developing and various methods have emerged.…”
Section: Application Of Antibody Fragment In Cancer Imagingmentioning
confidence: 99%
“…These antibody fragments not only retain important ability to specifically bind antigen but also have more ideal half-life and penetration functions than mAbs. Immunoimaging agents, which are composed of antibody fragments coupled with radionuclides, fluorescent dyes, fluorophores, and nanoparticles, can achieve high-resolution and clearly visible tumour imaging in a variety of ways [17,18]. Moreover, antibody fragments can also be used for targeted-tumour treatments for a variety of methods.…”
Section: Introductionmentioning
confidence: 99%
“…Coupled with radionuclides, fluorescent dyes, or nanoparticles, antibody fragments serve as imaging modalities for noninvasive detection and staging of tumors, and the evaluation of the surface molecule portfolio of cancer cells. Moreover, fragment-based imaging provides additional information beneficial for treatment including real-time fluorescence-guided surgery [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%